2017
DOI: 10.3390/en10070906
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Fluidic Comparison between Sandwich Panels with Tetrahedral Lattice Cores Fabricated by Casting and Metal Sheet Folding

Abstract: This numerical study compares single-phase forced convective heat transfer between two sandwich panels with tetrahedral metallic lattice cores separately fabricated by investment casting and the more cost-effective metal sheet folding method. The numerical model is validated against available experimental data. For a given Reynolds number and core porosity, the results reveal that the brazed sandwich outperforms the casted sandwich, exhibiting a 13% to 16% higher Nusselt number. Bigger vertexes and more eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Thus, there is a need of using models, which are simplification of the real objects without losing adequacy to reality. In the numerical analysis of layered materials [17][18][19] and constructions, made from such materials, it is useful to perform a process called homogenization [20,21]. As a consequence, instead of structure of layers made from different materials one can obtain one layer characterized by effective properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a need of using models, which are simplification of the real objects without losing adequacy to reality. In the numerical analysis of layered materials [17][18][19] and constructions, made from such materials, it is useful to perform a process called homogenization [20,21]. As a consequence, instead of structure of layers made from different materials one can obtain one layer characterized by effective properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…For the fluid-solid coupling interface, a conservative interface flux condition is adopted for heat transfer by incorporating a general grid interface (GGI) mesh connection. Translational periodicity boundary condition with zero pressure drop is used on the periodic surfaces for both the solid domain and air domain 3,28 , with the other surfaces of the computational domain set to be adiabatic. Considering that the heat flux applied on the heating surface is not measured directly in the force convective experiment, its value is derived based on the measured heating temperature.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Gao 26,27 introduced a composite tetrahedral LFM and revealed the heat transfer mechanism by analysing the local thermal and fluid flow patterns. For a given porosity, Zhang 28 compared the thermal performance between square and circular cross-section tetrahedral lattice cores and determined that a 13% to 16% higher Nusselt number was achieved for square ligaments compared with circular ligaments, which was due to the complex flow mixing. In addition, the effect of porosity was studied by Karen 4 , and the results showed that the high Nusselt number increased as porosity decreased due to the increased surface area and flow mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [15] pointed out that the sandwich panels filled with X-type truss array and Kagome-type truss array have higher heat transfer performance. Zhang et al [16] stated that for the sandwich panels filled with tetrahedral truss structure, the heat transfer performance of the brazed sandwich panel and casted sandwich panel is nearly the same. The results reported by Jin et al [17] show that the X-type truss array structure has more advantages than the Pyramidal-type truss array structure in heat transfer capacity and comprehensive thermal performance.…”
Section: Introductionmentioning
confidence: 99%